KOPERASI SEBAGAI IMPLEMENTASI EKONOMI KERAKYATAN - Rosmiati, Eros (MAJALAH ILMIAH WIDYA, 2012)
Cooperation is a fellowship enterprise owned and managed cooperatively. Inflation that so far existed in Indonesia is markedby the inflation in food prices, which normally higher than the average level of inflation. That is why food inflation rate would normallybe used as an indicator in predicting the effects of the increasing number of poor people. The purpose of this paper is to recognizean alternative solution by developing Village Cooperation Unit (Koperasi Unit Desa) that focuses on the consumption market, the foodprices can be pushed down or stay steady with a target in a decrease in food inflation rate specifically and the average level of inflationgenerally. As the result, the number of poor people would also be decreased. The method used library research and analyzeddescriptively. It is concluded that by developing a village cooperation can be used to improve peopleâs economic system.